2019
DOI: 10.1016/j.childyouth.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for foster placement breakdown: The predictive value of the strengths and difficulties questionnaire and foster child and foster family characteristics

Abstract: UvA-DARE (Digital Academic Repository) Risk assessment for foster placement breakdown: The predictive value of the strengths and difficulties questionnaire and foster child and foster family characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…e results showed that the total effective rate of the differentiated nursing group was 96.05%, which was significantly higher than that of the conventional nursing group (80.26%) [14]. e total excellent and good rate of nursing compliance was significantly higher than that of the routine nursing group [15][16][17][18][19]. e analysis of the relevant reasons could be that we pay attention to the different conditions of patients with different peptic ulcers in the differentiated nursing mode, such as clinical condition, psychological state, and education level, and provide corresponding nursing care for patients in a different and pertinent manner, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 90%
“…e results showed that the total effective rate of the differentiated nursing group was 96.05%, which was significantly higher than that of the conventional nursing group (80.26%) [14]. e total excellent and good rate of nursing compliance was significantly higher than that of the routine nursing group [15][16][17][18][19]. e analysis of the relevant reasons could be that we pay attention to the different conditions of patients with different peptic ulcers in the differentiated nursing mode, such as clinical condition, psychological state, and education level, and provide corresponding nursing care for patients in a different and pertinent manner, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 90%